Padjadjaran University Library Services During The Covid-19 Pandemic - Putri Martina Nursinta; Sukaesih -; Evi Nursanti Rukmana; Samson CMS - (Universitas Airlangga, 2021)
The early onset of covid-19 in 2020 causes a complete shutdown of all activities including those of services in the library to avoid direct contact with users in order to prevent the spread of this covid-19 virus. The purpose of this study is to fulfill the tasks that teachers have given you and to find out what innovations the unpad library has made to serve students or other users in spite of this covid-19 pandemic. The study USES descriptive qualitative methods on concepts related to library science, as well as to analyze the practices used in libraries during the pandemic. Data obtained through interviews conducted by researchers by sending some questions through the email of the unpad central library staff. The data already obtained will be presented in a descriptive form, so it will outline the importance of providing online library services by applying digital predating concepts. By subscribing to multiple journals and e-book databases, information-related services are still needed to support student and lecturer research, in this case libraries can engage in inter-library cooperation. During the pandemic, a university library service was required to transform from manual services into digital services.Â